Bioanalytical method development and validation for the simultaneous estimation of Thiocolchicoside and Lornoxicam in human plasma and in pharmaceutical dosage form by RP-HPLC - Kumar P.; Shukla S.; Subudhi B.B.; Ganure A.L. (My University, 2025)
Combination therapy of Lornoxicam (LOR) and Thiocolchicoside (THC) is used in pain management. To obtain optimal drug concentrations (minimum effective concentrations) for pain suppression and avoidance of drug toxicity, monitoring of drug levels has been considered essential to determine drug concentrations in plasma A new reverse phase high-performance liquid chromatography (RP-HPLC) assay was developed for the simultaneous determination of Lornoxicam and Thiocolchicoside in human plasma as well as in pharmaceutical dosage form. The method involves a simple protein precipitation procedure that uses no solid-phase or liquid-liquid extraction. The compounds were separated by using a mobile phase of Phosphate buffer (pH 6.8) and Acetonitrile (70:30 v/v) in isocratic flow with flow rate 1 ml/min on an Phenomenex Luna S -C18 column (5 μm, 250mm X 4.60mm i.d.) with PDA detection at 295 nm. The retention time for Thiocolchicoside is 5.94 ± 0.2 min, for Lornoxicam 14.53 ± 0.2 min. Validation of the method was performed in terms of linearity, accuracy, and precision, limit of detection and limit of quantification. The method was validated over the range of 100-500 ng/ml for Thiocolchicoside (r2= 0.9983) and 200 -1000 ng/ml for Lornoxicam (r2= 0.9972) for both plasma and tablet dosage form. The limit of detection was 33.27 ng/mL for Thiocolchicoside and 66.2 ng/ml for Lornoxicam in human plasma, and the lower limit of quantification (LLOQ) of Thiocolchicoside and Lornoxicam in plasma was 100.82 and 200.48 ng/ml respectively. Extraction recoveries of the analytes in plasma were ranging from 83.43-91.57 % at three different levels of concentration (LQC, MQC, and HQC).So the assay is suitable for use in pharmacokinetic studies and routine plasma monitoring of this combination drug therapy in patients of musculoskeletal disorders.